IMPLEMENTATION OF BOX JAM LEARNING MEDIA IN MATHEMATICS INSTRUCTION TO ENHANCE STUDENTS CREATIVITY AT MI BAHRUL ULUM JOMBANG - Ummi Khoirotun Nisak; Intan Nadhiroh; Fitrotin Hasanah; Khoirur Roziqin (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2026)
This study aims to describe the implementation of Box Jam learning media in third-grade mathematics lessons at MI Bahrul Ulum Jombang and analyze its impact on improving student creativity. This study was motivated by students' low understanding of abstract time concepts and the limited use of concrete learning media in the classroom. The study used a descriptive qualitative approach with third-grade students in the 2025/2026 academic year and mathematics teachers as subjects. Data collection techniques included participatory observation, semi-structured interviews, and documentation. Data analysis was conducted using the interactive model of Matthew B. Miles, A. Michael Huberman, and Johnny Saldaña, which included data reduction, data presentation, and conclusion drawing. The results showed that the Box Jam media was able to help students understand the concept of time concretely through exploration and hands-on activities. Student creativity increased in terms of originality, flexibility, and elaboration. Challenges encountered included learning time management, difficulty understanding the 24-hour format, and differences in students' learning styles. The solutions applied by teachers included effective group management, the use of contextual examples, and storytelling methods. This study contributes to the development of concrete learning media that supports creativity and meaningful learning in madrasahs.